Feeding flaxseed to chicken hens changes the size and fatty acid composition of their chicks’ brains - Whittle, Rosemary H.; Kiarie, Elijah G.; Ma, David W. L.; Widowski, Tina M. (Frontiers in Physiology, 2024)
Diets fed to commercial chicken breeders are high in n-6 fatty acids (n-6 FA) and low in n-3 fatty acids (n-3 FA). N-3 FA are essential for embryonic brain development. In precocial birds, like chickens, brain development and brain n-3 FA accrual occur primarily before hatching. In two experiments, broiler and layer breeders were fed diets with or without flaxseed as the source of n-3 FA from plant-based alpha-linolenic acid. Day-old broiler (n=80) and layer (n=96) offspring were dissected to calculate the percentage brain-to-body weight ratio. Brain FA analyses from total lipid extracts were determined in the broiler (n=24) and layer (n=24) offspring brains, and percentage FA composition and concentration (µg FA per g brain) were calculated for each n-3 and n-6 FA. Brain size was only increased in broiler offspring from mothers fed flaxseed (χ2=9.22, p=0.002). In layer offspring only, the maternal flaxseed diet increased the brain concentration and percentage of n-3 FA and decreased n-6 FA (p<0.05). We showed that feeding flaxseed to mothers increased brain size in broiler offspring and altered brain FA composition in layer offspring. These results may have implications for poultry and other captive bird species fed diets low in n-3 FA.